Reception tests of the WEST PFUs using ultrasonic testing and infrared thermography. (September 2022) - Ramaniraka, M.; Richou, M.; Vignal, N.; Addab, Y.; Missirlian, M.
Highlights: This study compiles the results of the acceptance and reception tests of the 456 WEST plasma facing units (PFUs). Ultrasonic testing, infrared thermography (IR) and high heat flux (HHF) tests were achieved. All the 456 WEST plasma facing units (PFUs) received at CEA were inspected by ultrasonic testing (UT) by the manufacturer. Based on UT results, all the delivered WEST PFUs are compliant with the acceptance criteria. Reception tests (IR, HHF) lead to confirm that most of the delivered PFUs have the required thermal solicitation handling capability. HHF results obtained on WEST PFUs are fully consistent with the IR results. 108 PFUs (24%) were tested using IR. 8 PFUs ( ∼ 7% of the tested PFUs) revealed thermal imperfections. Abstract: This study compiles the results of the acceptance and reception tests of the 456 WEST plasma facing units (PFUs) using ultrasonic testing, infrared (IR) thermography and high heat flux (HHF) tests. The actively cooled PFU, based on manufacturing technologies options foreseen for the ITER divertor target, is constituted of 35 tungsten blocks joint to CuCrZr tube via Cu-OFHC interlayer. The typical defect leading to an adequate heat exhaust of the component is the debonding at blocks interfaces between CuOFHC interlayer and CuCrZr pipe. A maximum size of defect, measured with ultrasonic testing, was defined as a condition of the acceptance of components from the manufacturer. All the 456 PFUs received at CEA were inspected by UT by the manufacturer and are compliant with the acceptance criteria. Reception tests led by CEA (IR, HHF) confirm that most of the delivered PFUs have the required heat load handling capability. 108 PFUs were tested using IR. Eight PFUs (∼7%) revealed thermal imperfections on 46 blocks, one PFU concentrating thermal imperfections on all its blocks. The proportion of blocks with defect detected by IR among all the 108x35 blocks is low (1.2%). Among the eight PFUs with detected defects, four of them have imperfections only on the blocks located at PFU's extremity. Those PFUs were installed in WEST as the blocks are located in a zone with negligible heat load. About the four other PFUs, the detected defects are located at different zones and UT did not detect any imperfection on them. To evaluate the possibility of installing these PFUs in WEST, HHF tests are used. The HHF results are fully consistent with the IR results.